Characterisation of flame-generated soot and soot-in-oil using electron tomography volume reconstructions and comparison with traditional 2D-TEM measurements. (December 2016) - Orhan, O.; Haffner-Staton, E.; La Rocca, A.; Fay, M.
Abstract: This work characterises soot nanoparticles by electron tomography using Weighted Back Projection algorithm and appraises the uncertainties in two-dimensional calculations by comparison with 3D parameters for flame-generated soot and diesel soot-in-oil. Bright field TEM was used to capture 2D images of soot. Large uncertainties exist in 2D-measured morphological parameters. The flame-generated particle showed an extensive 3D structure while the soot-in-oil was notably two-dimensional. Morphological parameters of flame-generated soot and diesel soot-in-oil were different; primary particles, volume, and surface area varied significantly over the range of viewing angle, with differences as large as 60%. 2D flame-generated soot volume underestimated 3D measurements by 38%; soot-in-oil 2D- and 3D-derived volumes were within 4%. 2D calculations of fractal dimension generally underestimate the 3D value. Highlights: Electron tomography was used as a technique to characterise carbon black and soot-in-oil. Flame-generated particle showed an extensive 3D structure. Soot-in-oil particle was notably two-dimensional. Morphological parameters varied significantly over the range of viewing angle. 2D calculations of fractal dimension generally underestimate the 3D value.